Analysis Factors Related with Succesful in Exclusive Breasfeeding During Pandemic - Baharika Suci Dwi Aningsih; Dewi Novitasari Suhaid (Journal of Midwifery, 2023)
Exclusive breasfeeding is one of the Sustainable Development Goals programs that aim to provide good nutrition for babies naturally. Given the far-reaching benefits of exclusive breastfeeding for babies, mothers and the economy, concerted efforts are needed to meet the World Health Assembly (WHA) target of at least 50% exclusive breastfeeding for 6 months by 2025. The exclusive breastfeeding coverage rate is still far from the expectations removed. This is to be expected as only 1 in 2 babies under 6 months are exclusively breastfed. This shows that almost 50% of Indonesia's child population does not receive the nutrition they need in the first two years of life. The WHO reports that more than 40% of infants were introduced to complementary foods before the age of 6 months and were given food that did not meet their nutritional needs. The aim of this study is to analyze factors related with successful in exclusive breastfeeding during a pandemic. This research is an observational, analytic, cross-sectional study. The sample in this study were mothers whom have toddlers aged 6-18 months from January 2020 to July 2021. The number of samples is 138 people. Data analysis will use the Chi Square test, fisher, and logistic regression. The results showed that the spacing pregnancy (p value = 0.010), Covid-19 infection during delivery or breastfeeding (p value = 0.017), and knowledge (p value = 0.013) had a significant relationship with exclusive breastfeeding. The dominant factor influencing exclusive breastfeeding is knowledge. The probability of logistic regression is seen with a value of 0.99